Consumer preferences and willingness to pay for new seedless lemon varieties in Turkey - Osman Sedat Subas; Hasan Çelen; Deniz Aksoy; Osman Uysal (Revista Brasileira de Fruticultura, 2024)
Abstract: It is crucial for the sustainability of research that the varieties obtained due to the various development activities carried out with public financing are put on the market correctly. This study it is aim to analyze the factors affecting consumer preferences and willingness to pay for lemons and newly developed seedless lemons throughout Turkey. The ordered probit model was estimated using online questionnaires from 566 consumers. There is a positive relationship between the monthly income, occupation, place of residence, age, and the dependent variable. It was determined that the variables of education and the number of family members were not statistically significant. It has been determined that 54.9% of consumers will not pay extra for seedless lemons, and 33.9% are willing to pay up to 10% more. In addition, it has been determined that subjects such as “juiciness” and “freshness” are more critical among consumers’ lemon purchasing criteria, while the number of seeds is less critical. It has been concluded that most consumers will prefer seedless lemons in the consumption of table lemons, but they will not be willing to pay more.